Crafting Sustainable Futures for Religious Destinations : A Research Perspective - Ravichandran, Sabari Shankar (Prabandhan: Indian Journal of Management, 2025)
Purpose : The research perspective addressed the sustainability challenges by looking into the multifaced motives of religious tourists and how these influenced the sustainability of religious destinations. Some gaps were identified regarding the interplay between tourist behavior, destination branding, and sustainability. Methodology : This perspective drew upon literature insights and expert interviews through Scopus-indexed research papers, industry data from Statista and The Business Research Report, and critical reflections. The analysis was based on the discussions of 15 experts, including academics, marketers, and policymakers, highlighting research gaps in governance and sustainability in religious tourism branding. Findings : The paper identified regenerative tourism, emphasizing destination quality improvements as a transformational response to degradation and overuse of resources. Food tourism was also found as a suitable alternative for consumption, aligned with cultural and sustainability objectives. Implications : The findings provided actionable strategies for destination marketers and policymakers in integrating sustainability into destination branding and governance structures. This perspective is aligned with global sustainable development goals, providing a foundation for future research and interventions to ensure the long-term resilience and viability of religious destinations.